Evaluación técnico-financiera del proceso de fitorremediación con plantas gramíneas para mitigar derrames de crudo en el departamento del Meta, Colombia (2018)
The present study is developed in the oil bioremediation area, through a laboratory test with a member of the gramineae species, the Brachiaria Bryzantha, this development is made with two different types of crude oils with different API gravities called "Crudo Acacias" and "Crudo Castilla", each one with four samples, one of these is the reference or control sample, where there won't be grass plants established and in this way evaluate the phytoremediation as oil spill method in the Department of Meta, Colombia. Besides, an investigation about the oil spill remediation methods used at national and international level and the technical and financial evaluation is done with a comparison between the results obtained from the laboratory tests and the ones obtained in previous studies that address the subject and with the soil remediation method that ATPingenieria uses in the present moment, Soil Washing.